Building service businesses in Africa: Introducing the business builder model. (13th August 2019) - Aksoy, Lerzan; Allerstorfer, Peter; Cadet, Fabienne; Cook, Paul; Keiningham, Timothy; Koser, Manuel
Abstract: The success of Silicon Valley has served as a driving force for entrepreneurs and investors worldwide. Many have attempted to create their own version in developing markets by setting up Silicon Valley‐style tech incubators. In recent years, Africa has seen an influx of these start‐up incubators, which has resulted in an emergence of major tech hubs in different parts of the continent. These areas have taken on names synonymous with the booming tech industry: Cape Town in South Africa is known as the Silicon Cape, Nairobi in Kenya as the Silicon Savannah, and Lagos, Nigeria as the Silicon Lagoon. Despite the influx and success of some of these incubators, there is also a multitude of examples where success and longevity are rare. The lifespan of these start‐ups are short and they seldom realize any profit. Limited access to capital markets, poor infrastructure, and weak regulatory environment are just a few reasons cited for this. Although there is a multitude of articles and publications that feature success cases and reasons behind propelling success, there are far fewer that focus on failures. As such, with this article we aim to shed light on the various reasons why these businesses fail by analyzing the literature and demonstrating them with real‐world examples of both successes and failures in the market. Using the information analyzed, we then propose a solution for successfully investing in tech startups in the developing world, the business builder model.